Regional Innovation Index of China: 2017 How Frontier Regions Innovate - Liu, Xielin; Gao, Taishan; Wang, Xi (Springer Nature Singapore : Imprint: Springer, 2018)
XVI, 342 p. 224 illus., 137 illus. in color.